No gene-by-environment interaction of BDNF Val66Met polymorphism and childhood maltreatment on anxiety sensitivity in a mixed race adolescent sample. Issue 1 (1st January 2018) - Martin, Lindi; Hemmings, Sian Megan Joanna; Kidd, Martin; Seedat, Soraya
ABSTRACT: Background : Anxiety disorders in youth are attributable to multiple causal mechanisms, comprising biological vulnerabilities, such as genetics and temperament, and unfavourable environmental influences, such as childhood maltreatment (CM). Objective : A gene-environment (G x E) interaction study was conducted to determine the interactive effect of the BDNF Val66Met polymorphism and CM to increase susceptibility to anxiety sensitivity (AS) in a sample of mixed race adolescents. Method : Participants ( n =  308, mean age = 15.8 years) who were all secondary school students and who completed measures for AS and CM were genotyped for the BDNF Val66Met polymorphism. Hierarchical multiple regression analysis was conducted to assess G x E influences on AS. Age and gender were included in the models as covariates as age was significantly associated with AS total score ( p < .05), and females had significantly higher AS scores than males ( p < .05). Results : A main effect of CM on AS was evident ( p < .05), however, no main effect of BDNF genotype on AS was observed ( p > .05). A non-significant G x E effect on AS was revealed ( p < .05). Conclusions : Our results suggest that CM does not have a moderating role in the relationship between the BDNF Val66Met genotype and the increased risk of anxiety-related phenotypes, such as AS. Given the exploratory nature of this study, findings require replication in larger samples and adjustment for population stratification to further explore the role of BDNF Val66Met and CM on AS in mixed race adolescents.